2021
DOI: 10.2166/wh.2021.205
|View full text |Cite
|
Sign up to set email alerts
|

Multiple water source use in low- and middle-income countries: a systematic review

Abstract: The Joint Monitoring Programme (JMP) 2017 Update and Sustainable Development Goals (SDGs) Baselines report classified 71% of the global population as having access to ‘safely managed’ drinking water. Current global monitoring efforts to track access to safely managed drinking water rely on collecting information on the ‘primary’ source of drinking water. However, there is evidence that households often rely on multiple sources to meet their water needs in many low- and middle-income countries (LMICs). This sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 96 publications
2
40
0
Order By: Relevance
“…Overall, 93% of samples were from the same category of water source, but concordance was lower for Kiribati (73%) and Chad (79%) (Table S3). Multiple source use has previously been documented ( Daly et al. 2021 ), including in the Pacific ( Elliott et al.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, 93% of samples were from the same category of water source, but concordance was lower for Kiribati (73%) and Chad (79%) (Table S3). Multiple source use has previously been documented ( Daly et al. 2021 ), including in the Pacific ( Elliott et al.…”
Section: Methodsmentioning
confidence: 99%
“…While there is a growing literature around the activities that universities are undertaking in this regard (Chankseliani and McCowan, 2021), few literature reviews synthesize these scholarly resources. Reviews of this topic have mostly focused on: business schools (García-Feijoo et al, 2020); a single nation (Owusu-Agyeman, 2020); a single university mission (e.g., teaching and not research) (Alonso-Garcia et al, 2019;Chiba et al, 2021;Weiss and Barth, 2019); specific SDGs and issues like safe drinking water (Daly et al, 2021), or as a component of Education for Sustainable Development (and specifically SDG 4.7) (Ferrer-Estévez and Chalmeta, 2021). 1 While they highlight important issues, 1 In more detail, some reviews have a narrow focus.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Weiss and Barth (2019) scrutinized current research on the implementation of sustainability in curricula across countries. Lastly, Daly et al (2021) honed in on a particular sustainability issue-safe drinking water (SDG 6)-by tracking the research on multiple water source use for drinking water in low-and middle-income countries. To conclude, the recent literature review conducted by Ferrer-Estévez and Chalmeta (2021) adopted a broader focus by analyzing contributions that investigated the implementation of ESD and SDGs at different educational levels: from primary school to HEIs.…”
Section: Introductionmentioning
confidence: 99%
“…Current global drinking water monitoring statistics are primarily informed by household surveys, asking households to describe their primary source of drinking water . However, a recent systematic review revealed that households across low- and middle-income countries (LMICs) practice multiple water source use (MWSU) . Households may use multiple drinking water sources for various reasons, including seasonal changes in availability, insufficiencies in supply or breakdown, aesthetics, financial cost, and physical distance to source .…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent systematic review revealed that households across low- and middle-income countries (LMICs) practice multiple water source use (MWSU) . Households may use multiple drinking water sources for various reasons, including seasonal changes in availability, insufficiencies in supply or breakdown, aesthetics, financial cost, and physical distance to source . Daly et al also found that, in some cases, households in LMICs supplement an improved primary water source with unimproved water throughout the year, a practice referred to as “supplemental unimproved source use” (SUSU) .…”
Section: Introductionmentioning
confidence: 99%